Pemberdayaan Hukum dan Ekonomi untuk Ketahanan Pangan dan Ekonomi Kreatif di Desa Delas, Kecamatan Air Gegas, Kabupaten Bangka Selatan - Nadia Sri Rezeki; Eko Riyadi; Agung Pranata; Nurhayati Dzikri; Rani Purwasih; Winda Purnamasari; Tri Agustin; Nanda Amelia; Karisma Karisma; Alpian Akbar; Fariq Zabran Adha (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Community service activities through Pertiba University's Field Study Program (KKN) in Delas Village, Air Gegas Subdistrict, South Bangka Regency were carried out to raise legal awareness, strengthen food security, and develop a creative economy based on local potential. The methods used included legal socialization, education in schools, assistance with the digitization of MSMEs, chili and celery horticulture, turmeric and tamarind herbal medicine workshops, social services, and collaboration with Posyandu and the private sector. The results of the activities showed an increase in the community's understanding of law and the digital economy, an increase in skills in processing local products, and the emergence of motivation to develop household food security. This activity successfully strengthened the synergy between students, the community, the village government, and external partners. In conclusion, the program's objectives were achieved by providing positive impacts in the form of increased legal literacy, food self-sufficiency, and the strengthening of the creative economy in Delas Village.